Physician and Patients Relationship in Contemporary Times (Orthodox and Non-Orthodox): Highlighting the Consequential Outcomes (Journal of Management and Social Sciences, 2025)
Understanding the dynamics and outcomes of physician and patient’s relationship require a comprehensive review and synthesis of existing literature on the doctor-patient, nurse-patient, and pharmacist-patient relationships, including non-orthodox practices. This engagement analysed various interaction models and outcomes, referencing key studies and theoretical perspectives such as Talcott Parsons' functionalist view and Thomas, Szasz, and Hollender's therapeutic relationship situations. The main findings highlight that effective healthcare outcomes rely on the quality of relationships between patients and various healthcare providers. Socio-cultural compatibility, clear communication, and mutual trust significantly enhance these relationships, leading to better patient adherence, satisfaction, and overall health outcomes, particularly in diverse and socio-economically varied contexts like Nigeria. Therefore, the decision to use a health care facility when ill depends on a number of factors, including the perceived friendliness of the physician's demeanour, the efficiency and effectiveness of the services being provided, and how well-suited the therapeutic intervention is to the social status of users/health consumers government policies as important, necessary and inevitable even when such policies bring hardship on the masses.